PENGARUH PELAKSANAAN MODEL KOOPERATIF TIPE TGT (TEAM GAMES TOURNAMENT) TERHADAP KEMAMPUAN BERKOMUNIKASI SISWA KELAS V SDN 201 TAMMU-TAMMU - Nasriani Nasriani (Scolae: Journal of Pedagogy, 2020)
This study aims to describe the implementation of the TGT (Team Games Tournament) cooperative model, know thedescription of communication skills, examine the effect of the implementation of the TGT (Team Games Tournament)type cooperative model on the communication skills of students in class V of SD Tammu-Tammu. This research is aquantitative study using true experimental deisgn, namely the pretest-posttest control group design. In this study thereare two variables: the independent variable is the implementation of the TGT (Team Games Tournament) cooperativemodel and the dependent variable is the student's communication ability. The population in this study were 53 gradestudents of Tammu-Tammu 201 Elementary School, totaling 53 students. Furthermore, the determination of the sampleusing probability sampling with the type of simple random sampling is divided into two groups, namely theexperimental group and the control group of 20 students each. The instrument was validated by expert lecturers. Thedata obtained were analyzed with two types of statistics namely descriptive statistics and inferential statistics includingdata normality test, data homogeneity test and hypothesis testing with the help of SPSS for windows 20.The results of the analysis show that: (i) the implementation of the TGT (Team Games Tournament) type of cooperativemodel in social studies consists of the stages of class presentation, group learning, games tournaments and group awardsgenerally well implemented. (ii) the students 'communication skills in the experimental group before learning had anaverage score of students' communication skills of 69.85, after being taught by implementing the TGT (Team GamesTournament) type cooperative model an average score of 88.65 increased. In the control group before learning theaverage score of students' communication skills was 67.9 and after learning increased by 74.0. (iii) The implementationof the TGT (Team Games Tournament) cooperative model influences the communication skills of the fifth gradestudents of SD Negeri 201 Tammu-Tammu.